2018
DOI: 10.1007/s00415-018-9035-0
|View full text |Cite
|
Sign up to set email alerts
|

Worse endovascular mechanical recanalization results for patients with in-hospital onset acute ischemic stroke

Abstract: The recognition, assessment and pre-interventional procedures of patients with in-hospital strokes and subsequent mechanical thrombectomy are favorable. Nevertheless, in-hospital stroke patients display inferior recanalization results and poorer clinical outcomes. Furthermore, we find mechanical thrombectomy seems safe for treatment of in-hospital strokes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…6 Overall, patients with in-hospital stroke experience less improvement within 24 hours, show less improvement by discharge, are less likely to be able to ambulate independently on discharge, and are less likely to return directly home. 2,3,5,6,23,49 Analysis of the Get With The Guidelines and South London stroke registries showed that patients with in-hospital stroke were more likely to die in the hospital, and the South London registry reported a higher 5-year mortality for patients with inhospital stroke compared with patients with communityonset stroke. 10,50…”
Section: Discussionmentioning
confidence: 99%
“…6 Overall, patients with in-hospital stroke experience less improvement within 24 hours, show less improvement by discharge, are less likely to be able to ambulate independently on discharge, and are less likely to return directly home. 2,3,5,6,23,49 Analysis of the Get With The Guidelines and South London stroke registries showed that patients with in-hospital stroke were more likely to die in the hospital, and the South London registry reported a higher 5-year mortality for patients with inhospital stroke compared with patients with communityonset stroke. 10,50…”
Section: Discussionmentioning
confidence: 99%
“…Previous study showed that patients with in-hospital stroke who were treated with thrombolytics had higher rates of in-hospital mortality and post-thrombolytic intracerebral hemorrhage [8]. Also, patients with in-hospital stroke may have worse recanalization results and poorer clinical outcomes [9]. However, our case showed that mechanical thrombectomy seems safe for treatment of in-hospital strokes.…”
Section: Discussion/conclusionmentioning
confidence: 61%
“…Because most inpatient strokes occur in nonneurological departments, these delays are mainly due to either lack of awareness of stroke symptoms and nonspecific clinical features 1–3 . In previous studies, the time intervals between symptoms onset and primary physician notification of symptoms onset/stroke alerts activation occupied over 80% of the intervals delay for IHS patients 7,23 . It is impractical to expect nonneurology medical staff to fully grasp all items of NIHSS.…”
Section: Discussionmentioning
confidence: 99%